Enrichment of freshwater zooplankton Moina micrura with probiotics isolated from microalgae - Samat, Nur Amalina; Md Yusoff, Fatimah; Min, Chong Chou; Abd Karim, Murni Marlina (Triveni Enterprises, 2020)
Aim: The present study investigated the ability of probionts to enrich freshwater zooplankton, Moina micrura based on population density, population growth rate and mean body size increment. Methodology: Different concentrations of probionts were introduced to one-day-old female Moina in filter-sterilized freshwater pond water. Addition to probiont, Chlorella sp. was added in culture media as a food source. Results: Population density, population growth rates and increase in mean body size of Moina were observed and recorded to evaluate the ability of probiont to enrich Moina. All four probionts were able to enrich Moina in treatment PC 1 (104 CFU ml'1) and PC 2 (106 CFU ml'1) at a better rate compared to the control group (no probiont). Also, the specific population growth rate (pi) and mean body size of Moina in treatment PC 1 and PC 2 were significantly higher than in treatment PC 3 (10s CFU ml'1) and control for all probionts. Interpretation: All probionts were able to enrich Moina and increased their growth at lower concentrations (PC 1 and PC 2). Supplementation of probiont at high concentration was unnecessary.